Efficacy of antimicrobial photodynamic therapy versus antibiotics as an adjunct to scaling and root planing for the treatment of aggressive periodontitis: a systematic review - Gugale, Akanksha; Kothiwale, Shaila V.; Shaik, Shahanaz (International Journal Of Community Medicine And Public Health, 2024)
Treating aggressive periodontitis (AgP) is quite challenging. Conventional treatment for aggressive periodontitis involves systemic antibiotics (AB) with scaling and root planing (SRP). However, antimicrobial photodynamic therapy (aPDT) presents a promising alternative due to its targeted action and reduced side effects. This suggests the need to analyse and compare both treatments to determine the best approach for effective management of AgP. A systematic literature searches in three databases: PubMed, Google Scholar, and Cochrane, and a hand search of relevant scientific journals was performed. The eligible studies included randomized controlled trials (RCTs) with parallel-group design, comparing aPDT to AB as adjuncts to SRP for treating AgP. Studies published in English language between January 2003 and December 2023 were included. Studies were assessed for quality using the Cochrane risk-of-bias tool for randomized trials version 2 (RoB 2) and were classified as high-quality studies. Five RCTs meeting eligibility criteria were selected and underwent qualitative analysis. The clinical parameters assessed in studies were Pocket Probing Depth (PPD), Bleeding on Probing (BOP), and Clinical Attachment Level (CAL). Two studies reported significant improvements in all parameters with both therapies, three studies indicated a greater reduction in clinical parameters in the AB group compared to aPDT. Adjunctive use of AB with SRP results in significant clinical outcomes compared to SRP and aPDT. According to the studies of this systematic review 4-5 applications of aPDT with an interval of 7 days, and a follow-up period of 6 months are beneficial in treating AgP.